Video Mapping Sebagai Strategi Komunikasi Visual untuk Transformasi Institusional UNU Pasuruan - Zulkif, Senjaya Machfudi; Jamil, Amidatus Sholihat; Astuti, Eka Rini Widya; Zenmira, Kharisma Nanda (Lembaga Pengembangan Kinerja Dosen, 2026)
This study was designed to create a visual communication medium in the form of a video mapping depicting the institutional change process from the Nahdlatul Ulama Institute of Technology and Science (ITSNU) Pasuruan to the Nahdlatul Ulama University of Pasuruan (UNU Pasuruan). This institutional status change represents a strategic moment that needs to be communicated to the public through a creative and engaging media approach. The research approach used the Research and Development (R&D) method, referring to Sugiyono's development framework, which consists of ten stages: identification of potential and problems, data collection, product design, design validation, design refinement, product testing, product refinement, implementation trials, final product revisions, and mass production (if necessary). Data collection techniques included in-depth interviews, field observations, documentation studies, and validation by media and content experts. The research output is a video mapping product, approximately 7 minutes in length, that has undergone a validation process and is deemed suitable as a means of communicating institutional change. This product is expected to serve both as a visual archive and as a more effective and communicative institutional promotion instrument.